Adsorption of temperate phages of Lactobacillus delbrueckii strains and phage resistance linked to their cell diversity - Trucco, Verónica Milagros (2011)
Aims: The aim of this work was to study the adsorption step of two new temperate bacteriophages (Cb1/204 and Cb1/342) of Lactobacillus delbrueckii and to isolate phage-resistant derivatives with interesting technological properties. Methods and Results: The effect of divalent cations, pH, temperature and cell viability on adsorption step was analysed. The Ca2+ presence was necessary for the phage Cb1/342 but not for the phage Cb1/204. Both phages showed to be stable at pH values between 3 and 8. Their adsorption rates decreased considerably at pH 8 but remained high at acid pH values. The optimum temperatures for the adsorption step were between 30 and 40°C. For the phage Cb1/342, nonviable cells adsorbed a lower quantity of phage particles in comparison with the viable ones, a fact that could be linked to disorganization of phage receptor sites and/or to the physiological cellular state. The isolation of phage-resistant derivatives with good technological properties from the sensitive strains and their relationship with the cell heterogeneity of the strains were also made. Conclusions: Characterization of the adsorption step for the first temperate Lact. delbrueckii phages isolated in Argentina was made, and phage-resistant derivatives of their host strains were obtained. Significance and Impact of the Study: Some phage-resistant derivatives isolated exhibited good technological properties with the prospective to be used at industrial level.